1991
DOI: 10.1016/0003-6870(91)90310-e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of handle height on lower-back loading in cart pushing and pulling

Abstract: This paper presents results of a study conducted to estimate lower back loadings in cart pushing and pulling. Experiments were conducted in the laboratory using a cart. Six subjects with different weights (ranging from 50 to 80 kg) were tested for three different pushing and pulling forces (98, 196 and 294 newtons), three different heights of exertion (660, 1090 and 1520 mm high) and two different moving speeds (1.8 and 3.6 km/h). It was found that, in general, pushing a cart results in lesser lower-back loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 7 publications
5
64
2
Order By: Relevance
“…Only two studies were found that reported spinal shear forces (deLooze et al,1995;Schibye et al, 2001), but they failed to achieve consensus. Estimated values ranged from 100 to 1400 N, whereas published estimates of compressive load range from 500 N (Schibye et al, 2001) to 5500 N (Kumar, 1994;Lavender, Conrad, Reichelt, Johnson, & Meyer, 2000), with the large difference resulting from exertion level and experimental design (deLooze et al, 1995;Lee, Chaffin, Herrin, & Waikar, 1991;Resnick & Chaffin, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies were found that reported spinal shear forces (deLooze et al,1995;Schibye et al, 2001), but they failed to achieve consensus. Estimated values ranged from 100 to 1400 N, whereas published estimates of compressive load range from 500 N (Schibye et al, 2001) to 5500 N (Kumar, 1994;Lavender, Conrad, Reichelt, Johnson, & Meyer, 2000), with the large difference resulting from exertion level and experimental design (deLooze et al, 1995;Lee, Chaffin, Herrin, & Waikar, 1991;Resnick & Chaffin, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Since this relatively short handle height with respect to the tall subjects did not provide enough clearance between the legs and luggage to avoid heel-kicking of luggage, it might induce an awkward posture resulting in large moments in the shoulder and trunk. Kingma et al 21) , Jäger et al 30) , and Lee et al 35) also found that tall and heavy operators generally showed larger moments at the lower back than short and light operators when handling manual vehicles.…”
Section: Discussionmentioning
confidence: 96%
“…Selecting the faster luggage-pulling speed than the tall subjects, the short subjects might more concentrate on forward and backward movement than sideward to keep up the speed of the running belt. The speed of handling manual vehicles is directly proportional to physical workload 23,32,35,36) . Even 110 cm handle height that is longer than that of commercially available luggage may not be long enough for the tall subjects to have a natural posture during a luggage-pulling task.…”
Section: Discussionmentioning
confidence: 99%
“…8013 ". 148 . However, large contrasts are present between the aforementioned studies, and also in relation tot the present study, with respect to the level of compressive forces reported.…”
Section: Mechanical Load At the Low Backmentioning
confidence: 99%
“…Compressive and shear forces at the low back have mainly been estimated using single equivalent muscle models (SEM, e.g. 148 ). However, it is assumed that r pushing and pulling the validity of such models is low 6150 .…”
mentioning
confidence: 99%